Exposure to bisphenol A, chlorophenols, benzophenones, and parabens in relation to reproductive hormones in healthy women: A chemical mixture approach. (November 2018) - Pollack, Anna Z.; Mumford, Sunni L.; Krall, Jenna R.; Carmichael, Andrea E.; Sjaarda, Lindsey A.; Perkins, Neil J.; Kannan, Kurunthachalam; Schisterman, Enrique F.
Abstract: Background: Little is known about the associations of bisphenol A, chlorophenols, benzophenones, and parabens with reproductive hormone levels in women. Our goal was to evaluate the associations between repeated measures of these chemicals and their mixtures with reproductive hormones in women. Methods: Longitudinal urine samples from healthy, premenopausal women ( n  = 143 with 3–5 urine samples each) were measured for bisphenol A, five chlorophenols (2, 4-dichlorophenol (2, 4-DCP), 2, 5-dichlorophenol, 2, 4, 5-trichlorophenol, 2, 4, 6-trichlorophenol, triclosan), two ultraviolet (UV) filters (benzophenone-1, benzophenone-3), and eight parabens and their metabolites (benzyl, butyl, ethyl, heptyl, methyl, propyl, 4-hydroxybenzoic acid (4-HB), 3, 4-dihydroxybenzoic acid (3, 4-DHB)) over two menstrual cycles. Estradiol, progesterone, luteinizing hormone (LH), and follicle stimulating hormone (FSH) were measured in blood up to 8 times each menstrual cycle. Linear mixed models were used for both single and multi-chemical exposures estimated using principal component analysis. Four factors were identified including: paraben; paraben metabolites and BPA, phenols, and UV filters. Models were adjusted for creatinine, age, race, and body mass index and weighted with inverse probability of exposure weights to account for time varying confounding. Results: In single-chemical models, 3, 4-DHB was associated with estradiol (0.06 (95% confidence interval (CI): 0.001, 0.12)), 2-4-DCP with increased progesterone 0.14 (0.06, 0.21) and decreased FSH −0.08 (−0.11, −0.04), and 4-HB was associated with increased FSH 0.07 (0.01, 0.13). In multi-chemical models, all factors were associated with increased progesterone (beta coefficient range: 0.15 for UV filter factor to 0.32 for paraben factor). The paraben factor and the paraben metabolite and BPA factor were associated with increased estradiol [0.21 (0.15, 0.28); 0.12 (0.07, 0.18)]. The phenol and UV filter factors were associated with decreased estradiol, FSH, and LH. The UV filter factor showed the strongest inverse association with estradiol −0.16 (−0.22, −0.10), FSH −0.12 (−0.17, −0.07), and LH −0.17 (−0.23, −0.10). Conclusion: Mixtures of phenols were associated with changes in reproductive hormones. Such changes could contribute to adverse health in women but additional research is necessary. Highlights: Bisphenol A, chlorophenols, UV filters, parabens linked with reproductive hormones. Parabens factors associated with increased estradiol. Phenol and UV filter factors associated with decreased estradiol, FSH, and LH. In single chemical models, paraben metabolites associated with hormones.